Trust-Region Method for Load Flow Solution of Three-Phase Unbalanced Electric Power Distribution System. (17th January 2022) - Gianto, Rudy; Purwoharjono,
Abstract : At present, the electric power system is getting bigger and more complex, and its loading is also increasing. As a consequence, planning, operation, and control of the power system also become more complicated. It is known that system planning and operation are mostly based on the steady-state condition of the power system, and the system steady-state condition can only be determined from the load flow study. Thus, the development of a reliable and efficient method to solve the load flow problem is necessary so that the system steady-state condition can properly be evaluated. Since the characteristics of the electric distribution system are different from those of the transmission system, special treatments are usually required in the distribution system load flow (DSLF) analysis. In this context, several interesting techniques have been proposed in the analysis. In this paper, the application and extension of the trust-region method to solve the three-phase DSLF problem are proposed and investigated. Case studies using 19-node, 25-node, and 123-node distribution systems are also given in this paper. Results of the studies show that the output values obtained by the proposed method are in excellent agreement with those obtained by previously published methods. These results confirm the validity of the proposed method. Case study results also indicate that the proposed method has better computational performances than the forward/backward sweeping (FBS) method.